N-Acetylcysteine Treats Spinal Cord Injury by Inhibiting Astrocyte Proliferation - Dong Zhang; Chaoxi Qin; Fei Meng; Xiaopeng Han; Xing Guo (Analytical Cellular Pathology)
Astrocyte proliferation commonly occurs after spinal cord injury (SCI). N-Acetylcysteine (NAC) has a regulatory effect on many diseases. In this study, we investigated the effect and underlying mechanism of NAC on astrocytes in SCI. We isolated rat primary astrocytes and stimulated with lipopolysaccharide to induce cell proliferation and degeneration. A rat model of SCI was also established, and the Basso–Beattie–Bresnahan score was determined. The localization of glial fibrillary acidic protein in the cells and tissues was determined using TUNEL staining and immunofluorescence, while that of connexin 43 was assessed via immunofluorescence. Pathological changes associated with SCI were detected using hematoxylin and eosin staining, and inflammatory factors were detected using enzyme-linked immunosorbent assay. Additionally, JAK/STAT expression was evaluated using western blotting and quantitative reverse transcription polymerase chain reaction. NAC downregulated the glial fibrillary acidic protein abundance and connexin 43 in reactive astrocytes and SCI rat models while inhibiting the abundance of secreted proteins DSPG, HSPG, KSPG, tenascin C, vimentin, CSPG, ephrin-B2, and nestin. NAC also regulated the JAK/STAT signaling pathway by downregulating the expression of JAK2, STAT5, STAT3, STAT1, PIM1, NFATc1, COL1, COL3, TGF-β, SMAD1, CTGF, CyCD1, and CDK4, thus alleviating SCI. Finally, NAC exhibited durable effects, with no SCI recurrence within 60 days. Therefore, NAC relieves SCI by inhibiting the proliferation of reactive astrocytes and suppressing the expression of secretory and JAK/STAT pathway proteins.